A Study on Korean peninsula peaceful unification process - Piri, Ali (KDI School, 2000)
This monograph examines the question of what scenario would be more applicable for the Korea Peninsula unification process? Today North Korea appears to be on the verge of disintegration due in large part to philosophy of Juche or self-reliance, the disastrous flooding of 1995 resulting in widespread famine, and disproportionate military spending at the expense of economic development and social welfare. In this regard Four scenarios are advanced; Soft landing and Hard landing. First scenario, Collapse and absorption, Second, Unification through conflict, Third, Potential external intervention, and Forth, Kim Jong Il remains in power but recognizes that his power is too weak and that can no longer effectively govern. In this case he will seeks reunification accordance with the South Korea’s long term reunification.
Thesis(Master) --KDI School:Master of Public Policy,2000